The Influence of Contemporary Architecture on The Shape of Library Buildings and Fine Arts Education Facilities in Surabaya - Hariamin, Berliansan; Poedjioetami, Esty; Hendra, Failasuf Herman (Journal of Civil Engineering, Planning and Design, 2024)
A library and fine arts educational facility is an educational place to gain knowledge and introduce fine arts. Through observations, the researcher identified issues in Surabaya's libraries, such as the monotonous building structures and unattractive spatial atmosphere. Meanwhile, fine arts facilities lack resources for making art, so the integration of a library and fine arts education facility is necessary in one location. In this building, visitors can not only gain knowledge about art but also increase their creativity by learning while making works of art with artists. It serves as a solution to increase the reading interest index and introduce works of art more widely.The application of a contemporary architectural theme is based on the expressive characteristics of educational and artistic buildings, following current contemporary characteristics. Qualitative research with a descriptive approach depicts the experiences in the field, which were then analyzed using parameters of the function and feasibility of educational and artistic buildings.The design of the library and fine arts education facility applies the contemporary architecture theme to the macro concept of recreational education to provide a special attraction to visitors.The shape design uses an attractive micro concept by giving the building an identity through variations of curved lines, geometric shapes inspired by a book, and bright color combinations derived from mosaic paintings.